Imaging DOAS for volcanological applications - Louban, I.; Bobrowski, N.; Rouwet, D.; Inguaggiato, S.; Platt, U. (Sringer, 2009)
The simultaneous quantitative determination of two-dimensional bromine monoxide (BrO) and sulphur dioxide (SO2) distributions in volcanic gas plumes is described. Measurements at the fumarolic field on the island Vulcano (autumn 2004) and in the plume of Mt. Etna volcano (spring 2005) were carried out with an Imaging DOAS instrument. The SO2 fluxes of several fumaroles were estimated from two-dimensional distributions of SO2. Additionally, the first two-dimensional distributions of BrO within a volcanic plume were successfully retrieved. Slant column densities of up to 2.6×1014 molecules per square centimetre were detected in the plume of Mt. Etna. The investigation of the BrO/SO2 ratio, calculated from the two-dimensional distributions of SO2 and BrO, shows an increase from the centre to the edge of the volcanic plume. These results have significance for the involvement of ozone during BrO formation processes in volcanic emissions. Published 753-765 2.4. TTC - Laboratori di geochimica dei fluidi JCR Journal reserved